Accommodations in the Assessment of Health Professionals at Entry-to-Practice: A Scoping Review - Newhook, Dennis (Université d'Ottawa / University of Ottawa, 2018)
This scoping review examines the available evidence supporting accommodation use in the assessment of health professionals with disabilities in licensing contexts. While test accommodations are a protected right under antidiscrimination legislation, the peer-reviewed evidence informing their use is contested and widely dispersed. Furthermore, the ramifications of accommodation misuse are significant, including human rights violations and increased risks to patients. As such, this study addressed two research questions: 1) What is the current state of literature on accommodation use in the assessment of health professionals? and 2) What programs of research would address stakeholders’ concerns about the use of accommodations in the assessment of those professionals? Systematic searches of five prominent databases identified 15 articles for analysis. Several major themes emerged from that analysis: interpreting legislation, administration and process, relationships between education and licensure, and psychometrics and test development. Stakeholder consultation revealed that stakeholders face challenges managing accommodation requests and defining reasonable accommodations. While there is a paucity of literature on the topic overall, especially of an empirical nature, this study mapped the available evidence and laid the foundation for future studies by delineating the gaps in the scholarly literature as defined by stakeholders’ needs.
Keywords: accommodations; disability; health professions education; licensing; examination; scoping review